ترجمة المتلازمات اللفظية بين العربية والإنجليزية في النص الأدبي النثري : دراسة تحليلية لترجمة رواية رجال في الشمس لغسان كنفاني - إبراهيم، أمنية أحمد عبد الونيس (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims at addressing the phenomenon of Collocations in prose texts and their translation into English by analyzing a set of collocations selected from the Arabic novel “Men is the sun” by Ghassan Kanfani and comparing them to the English translation by Hilary Kilpatrick, an English author and translator, in her book “Men In The Sun and Other Palestinian Stories”. The goal of the study is to identify how the translator dealt with the Arabic collocations contained in the novel, as well as identify the various translation techniques used by the translator to transmit the Arabic collocations and their meanings and maintain their grammatical, semantic and lexical characteristics. The researcher selected 45 Arabic collocations and their English translation to be analyzed. The selected colocations were divided into 3 groups, 15 nominal, 15 verbal and 15 prepositional collocations. The study is constructed on the model of Hassan Ghazalah in terms of the grammatical structure which was modified to make it more specific. The researcher followed an analytical descriptive approach and used a set of Arabic and English dictionaries to analyze and describe the selected Arabic collocations and their translation. The study showed that the translator had used 7 various translation techniques. The most widely used technique was the free translation and the least used technique was the literal translation. The study also showed that the translator was concerned, in the first place, about transmitting the meaning of the Arabic collocations by finding English equivalents by using the free translation technique every time she found an English equivalent. However, she used other techniques when she couldn't find equivalents, such as interpretation, approximate equivalents and literal translation. The study concluded that the translator was often unable to maintain the Arabic collocations' grammatical structures due to the linguistic differences between Arabic and English.